VeritasPrepKarishma wrote:
irus wrote:
why 1/16 can someone explain pls
\(3*r^4 = \frac{2}{s}\)
\(s= \frac{2}{3*r^4}\) (multiply by s and divide by 3r^4)
What happens when r becomes 2r.
You get \(\frac{2}{3(2*r)^4} = \frac{2}{3*16*r^4}\)
How is this new expression different from the old one? The new one = Old one * (1/16)
Hence, s gets multiplied by 1/16 when r becomes twice.
Hi Karishma,
I have a small doubt here , I kept r to the left and s to the right and worked at it that way , below is the working :
Given \(3 r^4 = \frac {2}{s}\)
now r is doubled
\((2r)^4 =\frac{2}{3s}\)
\(16r^4= \frac{2}{3s}\)
Now the above can be rearranged as \(3r^4= \frac{2}{16s}\)
on comparing this with the original it seemed that s is being multiplied by 16 when r is doubled , hence I chose E. What is the error in the logic here?
s is in the denominator. You cannot say what it multiplies by.
To know "s is multiplied by ...", you need to separate out the s.